Optimizing Escherichia coli strains and fermentation processes for enhanced L-lysine production: a review - Wu, Zijuan; Chen, Tianpeng; Sun, Wenjun; Chen, Yong; Ying, Hanjie (Frontiers in Microbiology, 2024)
lysine is an essential amino acid with significant importance, widely used in the food, feed, and pharmaceutical industries. To meet the increasing demand, microbial fermentation has emerged as an effective and sustainable method for L-lysine production. Escherichia coli has become one of the primary microorganisms for industrial L-lysine production due to its rapid growth, ease of genetic manipulation, and high production efficiency. This paper reviews the recent advances in E. coli strain engineering and fermentation process optimization for L-lysine production. Additionally, it discusses potential technological breakthroughs and challenges in E. coli-based L-lysine production, offering directions for future research to support industrial-scale production.